Construction companies and corporate social responsibility: is it possible? - Domínguez Díaz, Ana María (Universidad de Sonora, 2020)
Construction companies, given the activity they carry out, should carry out an active social responsibility policy. In order to know if this is the case, a review of the literature on the matter has been carried out, which includes the behavior of these companies in different countries and over a long period of time, observing that these companies, for the most part, do not still integrated good practices in matters of social and environmental responsibility. However, there seems to be some concern on their part, although they still have a long way to go until construction companies can be seen as socially responsible.